Preparation and evaluation of cyclodextrin polypseudorotaxane with PEGylated liposome as a sustained release drug carrier - Hayashida, Kayoko; Higashi, Taishi; Kono, Daichi; Motoyama, Keiichi; Wada, Koki; Arima, Hidetoshi (Beilstein Journal of Organic Chemistry, 2014)
Cyclodextrins (CDs) can form polypseudorotaxanes (PPRXs) with drugs or drug carriers possessing linear polymers such as polyethylene glycol (PEG). On the other hand, PEGylated liposomes have been utilized as a representative anticancer drug carrier. However, little is known about the formation of CD PPRX with PEGylated liposome. In the present study, we first report the formation of CD PPRX with PEGylated liposome and evaluate it as a sustained release drug carrier. PEGylated liposome encapsulating doxorubicin was disrupted by the addition of α-CD. Meanwhile, γ-CD included two PEG chains and/or one bending PEG chain of PEGylated liposome and formed PPRX without the disruption of the membrane integrity of the PEGylated liposome. Moreover, the release of doxorubicin and/or PEGylated liposome encapsulating doxorubicin from the PPRX was prolonged in accordance with the matrix type release mechanism. These findings suggest the potential of γ-CD PPRX as sustained release carriers for PEGylated liposome products.
Keywords: cyclodextrins; doxorubicin; PEGylated liposome; polypseudorotaxane; sustained release